The Effect of Cell Surface Expression and Linker Sequence on the Recruitment of Arrestin to the GIP Receptor - Al-Sabah, Suleiman; Adi, Lobna; Bünemann, Moritz; Krasel, Cornelius (Frontiers in Pharmacology, 2020)
The glucose-dependent insulinotropic polypeptide (GIP) and the glucagon-like peptide-1 (GLP-1) receptor are important targets in the treatment of both type 2 diabetes mellitus (T2DM) and obesity. Originally identified for their role in desensitization, internalization and recycling of G protein-coupled receptors (GPCRs), arrestins have since been shown to act as scaffolding proteins that allow GPCRs to signal in a G protein-independent manner. While GLP-1R has been reported to interact with arrestins, this aspect of cell signalling remains controversial for GIPR. Using a fluorescence resonance energy transfer (FRET)-based assay we have previously shown that yellow fluorescent protein (YFP)˗labelled GIPR does not recruit arrestin. This GIPR-YFP construct contained a 10 amino acid linker between the receptor and a XbaI restriction site upstream of the YFP. This linker was not present in the modified GIPR-SYFP2 used in subsequent FRET and bioluminescence resonance energy transfer (BRET) assays. However, its removal results in the introduction of a serine residue adjacent to the end of GIPR’s C˗terminal tail which could potentially be a phosphorylation site. The resulting receptor was indeed able to recruit arrestin. To find out whether the serine/arginine (SR) coded by the XbaI site was indeed the source of the problem, it was substituted with glycine/glycine (GG) by site˗directed mutagenesis. This substitution abolished arrestin recruitment in the BRET assay but only significantly reduced it in the FRET assay. In addition we show that the presence of a N-terminal FLAG epitope and influenza hemagglutinin signal peptide were also required to detect arrestin recruitment to the GIPR, most likely by increasing receptor cell surface expression. These results demonstrate how arrestin recruitment assay configuration can dramatically alter the result. This becomes relevant when drug discovery programs aim to identify ligands with ‘biased agonist’ properties.